High-sensitivity lateral flow immunoassay with a fluorescent lanthanide nanoparticle label - Teppo Salminen; Etvi Juntunen; Sheikh M. Talha; Kim Pettersson (Elsevier B.V., 2022)
Lateral flow (LF) immunoassays are commonly used for point-of-care testing and typically incorporate visually read reporters, such as gold particles. To improve sensitivity and develop quantitative LF immunoassays, visual reporters can be replaced by fluorescent reporters detected by an instrument. In this study, we used fluorescent europium(III) chelate doped nanoparticle (Eu-np) reporters to develop a quantitative high-sensitivity LF immunoassay for free prostate specific antigen (fPSA). Furthermore, we tested different simplified formats of the assay and the effect of different modifiable parameters on the detection limit of the assay: dynamic range, assay duration and number of assay steps. The molar detection limits of the different assay formats were compared with published detection limits of LF immunoassays with different reporters. The cutoff was calculated from 11 female serum samples. The detection limit of the sensitivity optimized fPSA assay with fPSA spiked into pooled female serum was 0.01 ng/ml, which is approximately 100-fold lower than the most sensitive gold particle LF assays and 10-fold lower than other Eu-np and carbon nanoparticle based LF immunoassays. Thus, Eu-np reporters can be used to develop highly sensitive and quantitative LF immunoassays.